1) х=√2
х=1
2) х-6
Объяснение:
х⁴-х²-2=0
х²=т
т²-т-2=0
Д=в²-4ас
Д=1+8=9
х₁=
х₂=
т=х²
х=√2
2)
х²-11х+30=0
Д=121-120=1
х1=
х2=
=х-6
Смотри решение на фото
1) х=√2
х=1
2) х-6
Объяснение:
х⁴-х²-2=0
х²=т
т²-т-2=0
Д=в²-4ас
Д=1+8=9
х₁=![\frac{1-3}{2} =1](/tpl/images/1871/0721/45536.png)
х₂=![\frac{1+3}{2} =2](/tpl/images/1871/0721/50e42.png)
т=х²
х=√2
х=1
2)![\frac{x^{2} -11x+30}{x-5} =0\\](/tpl/images/1871/0721/2765c.png)
х²-11х+30=0
Д=в²-4ас
Д=121-120=1
х1=![\frac{11-1}{2} =5\\](/tpl/images/1871/0721/7dedf.png)
х2=![\frac{11+1}{2} =6](/tpl/images/1871/0721/9ad71.png)
Смотри решение на фото